Effect of slatted floor type on performance of swine grown during cold - Ames, D.; Brink, D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Average daily weight gain, feed consumption, and feed efficiency were determined for growing finishing swine reared on metal (aluminum) as opposed to plastic, slatted floor at ambient temperatures of 17, 32, 41 and 46 ̊ F. Performance was significantly (P<.05) improved with plastic slats at 17 and 32 F.
Swine Industry Day 1974 is known as Swine Day, 1974
Keywords: Swine; Slatted floor type; Performance; Growth